Erosion Bleeding as a Late Complication of Chest Wall Reconstruction with a Dacron Mesh Silicone Prosthesis - Sano, A.; Takeuchi, E.; Fukami, T.; Murakawa, T.; Nakajima, J. (The Thoracic and Cardiovascular Surgeon, 2012)
A 71-year-old man who had undergone chest wall resection and reconstruction with a Dacron mesh silicone prosthesis for chondrosarcoma 23 years previously presented with a chest wall hematoma. Since the hematoma was found to increase in size over time, we performed an operation to achieve hemostasis. Operative findings showed that the prosthesis had separated into three sheets.
Keywords: chest wall; sarcoma; reoperation; complications of surgery